Fine scale gene flow and individual movements among subpopulations of Centrolene prosoblepon (Anura: Centrolenidae) - M. Robertson, Jeanne (2008)
Dispersal capabilities determine and maintain local gene flow, and this has implications for population persistence and/or recolonization following environmental perturbations (natural or anthropogenic), disease outbreaks, or other demographic collapses. To predict recolonization and understand dispersal capacity in a stream-breeding frog, we examined individual movement patterns and gene flow among four subpopulations of the Neotropical glassfrog, Centrolene prosoblepon, at a mid-elevation cloud forest site at El Copé, Panama. We measured male movement directly during a two year mark-recapture study, and indirectly with gene flow estimates from mitochondrial DNA sequences (mtDNA). Individuals of this species showed strong site fidelity: over two years, male frogs in all four headwater streams moved very little (mean = 2.33 m; mode = 0 m). Nine individuals changed streams within one or two years, moving 675-1 108 m. For those males moving more than 10 m, movement was biased upstream (p < 0.001). Using mtDNA ND1 gene sequences, we quantified gene flow within and among headwater streams at two spatial scales: among headwater streams within two adjacent watersheds (2.5 km2) and among streams within a longitudinal gradient covering 5.0 km2. We found high gene flow among headwater streams (φST = 0.007, p = 0.325) but gene flow was more limited across greater distances (φCT = 0.322, p = 0.065), even within the same drainage network. Lowland populations of C. prosoblepon potentially act as an important source of colonists for upland populations in this watershed.